Ayurvedic Perspectives on Chronic Kidney Disease: A Review of Classical Wisdom and Contemporary Applications - Solanki Akshaykumar Vinodbhai; Ramakant Katara; H. M. L. Meena (AYUSHDHARA, 2025)
Chronic kidney disease (CKD) represents a progressive loss of renal function over time and poses significant challenges in global healthcare. In Ayurveda, CKD is understood as an Upadrava (complication) of urinary system disorders or systemic conditions such as Prameha (diabetes). This review explores the Ayurvedic perspective on CKD, focusing on its pathogenesis, prognosis, and therapeutic approaches. The disease is characterized by the vitiation of Dosha and their impact on Basti (renal system), leading to impaired filtration and systemic toxicity. Early stages are considered Krucchrasadhya (difficult to treat), whereas advanced stages are Yapya (manageable with palliation) or incurable. Management strategies in Ayurveda emphasize purification (Shodhana), pacification (Shamana), and rejuvenation (Rasayana) therapies. Detoxification procedures like Virechana and Basti therapy are employed to eliminate vitiated Dosha and restore systemic balance. Rasayana drugs such as Punarnava, Gokshura, and Shilajit enhance renal function, act as antioxidants, and provide nephroprotective effects. Clinical studies indicate improvements in digestion, vitality, and quality of life with these interventions. The integration of Ayurvedic principles, including dietary and lifestyle modifications, offers a holistic approach to CKD, addressing its systemic effects and slowing disease progression. This study underscores the potential of Ayurveda as a complementary and cost-effective therapeutic framework for CKD, particularly in resource-limited settings, by reducing reliance on conventional renal replacement therapies and improving patient outcomes.